The legislative and regulatory framework to accompany artificial intelligence systems - Solav Abdullah Hama Rashid (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The technological revolution, including the development of artificial intelligence and smart systems, represents a significant transformation in the digital age. Countries are increasingly relying on these systems to enhance their capabilities in data analysis and finding solutions to complex issues. This reflects the immense capabilities that mimic human intelligence, especially in areas that require complex thinking and precise analysis. Given these capabilities, it has become essential for countries, including Iraq, to integrate these systems in fields such as law and legislation. However, to ensure effective and correct integration of artificial intelligence systems, governments need to establish legislative and regulatory foundations that comply with the rules of using this technology. This requires a deep understanding of the legislative framework for artificial intelligence and how it impacts traditional legislations. There is an urgent need to develop and adapt traditional laws to fit the current technological advancements. In Iraq, it is necessary to highlight the role of legislators in the field of artificial intelligence and identify the legal mechanisms needed to enhance this legislative role. The efforts made in this area will help achieve effective integration between advanced technology and the legal and legislative framework, benefiting society and the economy at large. The study has found a rapid and noticeable development in the transition of society from traditional to digital systems, through a range of systems and applications that have entered all state institutions, including legal and judicial institutions. This implies the necessity of creating a legislative and legal environment to regulate the work of these systems and applications, licensing their operation, as well as the need to develop a strategy at the level of the Iraqi government to gradually transition to smart applications and systems for state management through the establishment of a legislative and legal framework to license their operation and develop legislation that meets the requirements of the current era.